Tuning of poly(ethylene terephtalate)(PET)surface properties by oxygen plasma treatment - Doliška, Aleš (Materiali in tehnologije, 2011)
Modification of surface properties of poly(ethyleneterephtalate) (PET) thin films by treatment with weakly ionized oxygen plasma was studied by contact angles of water and diiodomethane (DIM) drops. Samples were exposed to oxygen plasma with the ion density of 5 x 1015/msup3 and the neutral oxygen atom density of 3 x 1021/msup3. Just after the treatment they were characterized by contact angle measurements. Results showed a quick decrease of the water contact angle in the first few seconds of plasma treatment, while prolonged treatment did not cause any substantiated modification. The contact angles of DIM, on the other hand, remained rather constant for the first several secondsof plasma treatment, and increased after prolonged treatment. It was found that the dispersion component of the surface free energy decreased with increasing treatment time, while the polar component increased with treatment time. The results were explained by surface functionalization as well as by roughness effects.
Keywords: polietilen tereftalat; kisikova plazma; površinske lastnosti; stični kot; hidrofilnost; funkcionalizacija